Analisis Model Gerakan Anti-Tourism dalam Merespon Praktik Overtourism di Barcelona, Venice, Hawaii - Alimuddin, Ranty Yudhina; Rosnani, Rosnani (Universitas Bosowa, 2023)
Since a long time, tourism has been the main object of countries in the world. Tourism brings economic benefits, but then tourism development that does not have strategic planning causing several negative impacts. One of them is overtourism which leads to anti-tourism protest by local residents. This research used a qualitative method. The data collection technique was Literature Study by collecting all relevant information to the study. Researcher used the concept of social movements. The results show that the emergence of anti-tourism protest, especially on a large scale, is caused by lack of tourism management and issues that are generated from uncontrolled or sustainable tourism growth. Keywords: Overtourism, tourism, anti-tourism protest, social movements